MANAGEMENT ASPECTS OF BUSINESS DEVELOPMENT - Zhygalkevych, Zhanna (Journal of Strategic Economic Research, 2022)
The article examines the management aspects and algorithms for making managerial decisions for business development in modern conditions. The modern concept of management process as a cycle of consistent performance of basic management functions: planning, organization, motivation, communication and control is studied. The necessity of making a managerial decision for business development taking into account risky problem situations is substantiated from the practical point of view. It is determined that the need for management decisions may arise in connection with external circumstances: decisions of higher organization, the need to resolve relationships with cooperation partners, and internal: deviations from production parameters, bottlenecks, identification of reserves, violation of labor discipline. The concept of management decision space is studied and the experience of business owners taking into account the aspects and boundaries of such space is analyzed, and it is proved that each executor of management decision must have the best method of performing management tasks for business development. It is determined and substantiated that the management support of business development is that the management space system should have the same or greater variety and speed of action programs, which corresponds to the possible diversity of environmental influences on the system being managed.